UPAYA MENINGKATKAN KETERAMPILAN MENGGIRING PADA SEKOLAH DASAR - Iwan, Fransiskus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The purpose of this study was to determine the learning outcome dribble with plastic balls in class V students of State Elementary School 06 Weve Bemban Kecamantan South Pinoh Melawi. This research uses research